2005
DOI: 10.1002/jsfa.2143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary humate on the pH, TBARS and microbiological properties of vacuum‐ and aerobic‐packed breast and drumstick meats of broilers

Abstract: The current trial determined the influence of dietary humate, including humic, fulvic and ulmic acids and some microminerals on the pH, TBARS and microbiological properties of vacuum-packed and aerobic-packed breast fillets and drumsticks of broilers. A total of 240 male broiler chicks (Ross-308) were randomly allocated into four dietary treatments (H 0 , H 1 , H 2 and H 3 groups). A basal diet (H 0 ), basal diet plus 0.1 (H 1 ), 0.2 (H 2 ) and 0.3% (H 3 ) humate (Farmagulator DRY  , Humate, Farmavet Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 11 publications
3
13
0
2
Order By: Relevance
“…After 3 days of display storage, the pH of ground leg meat was significantly increased from 6.15 to 6.25, regardless of diet with or without probiotic ( P < 0.0001). An increase in the pH of chicken leg during postmortem storage has been reported in other studies . Kakouri and Nychas reported that an increased ammonia generation as microbial metabolites was observed from vacuum‐packaged chicken thigh meat during storage.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…After 3 days of display storage, the pH of ground leg meat was significantly increased from 6.15 to 6.25, regardless of diet with or without probiotic ( P < 0.0001). An increase in the pH of chicken leg during postmortem storage has been reported in other studies . Kakouri and Nychas reported that an increased ammonia generation as microbial metabolites was observed from vacuum‐packaged chicken thigh meat during storage.…”
Section: Resultssupporting
confidence: 73%
“…also reported that a greater increase in the pH value was found in aerobic packaged chicken drumsticks compared to vacuum‐packaged ones during chilled storage. Thus, the increased pH value after display storage could be likely related to the predominant growth of psycrotrophic bacteria producing nitrogenous metabolites, including ammonia …”
Section: Resultsmentioning
confidence: 99%
“…Weber et al (2014) suggested that HS in the diet of young pigs (0.25% for 35 days) may play a role in negating the effects of oxidative stress within the body. The inclusion of HS in the diets of broilers and growing pigs was found to reduce lipid peroxidation in muscle tissues during storage which had a positive effect on meat quality (Aksu et al 2005;Bai et al 2013). The in vitro study of Vaskova et al (2011) showed a decrease in the activity of superoxide dismutase; however, activities of other antioxidant enzymes were not influenced after HS treatment and HS-supported generation of ROS was not observed.…”
Section: Biomarker Of Oxidative Stressmentioning
confidence: 99%
“…This oxidative imbalance can result in immunosuppression with increased susceptibility to various diseases and in negative alterations in the growth performance of animals. Oxidative stress may also have a negative effect on meat quality and the shelf life of meat (Aksu et al 2005;Bai et al 2013).…”
mentioning
confidence: 99%
“…Recently, humic substances have been proposed as feed supplements to stimulate the growth of animals, to increase the nutritive value of feeds and as a potential replacement for antibiotic growth stimulators (Bailey et al, 1996;Shermer et al, 1998;Kocabagli et al, 2002;Yoruk et al, 2004;Aksu et al, 2005;Islam et al, 2005).…”
mentioning
confidence: 99%